Clinical and Biometric Evaluation of Guided Tissue Regeneration and Coronally Positioned Flap In Treatment of Grade II Forcation Defects In Mandibular Molars - : Pak Nejad M; Soleimani-; Mohammad Zadeh Z (Tehran University of Medical Sciences, 2000)
Guided Tissue Regeneration (GTR) is the most recent and common method for regeneration of class II forcation molars. However, it requires membrane, which seems expensive for most of the patients. In order to overcome this problem, Coronally Position Flap (CPF) procedure may be applied which arresting the epithelial cell down growth, follow the same aim. This study is aimed to compare GTR technique utilizing bioresorable collagen membrane and CPF utilizing citric acid. Nine patients with grade II forcation defects were selected. Defects were bilateral that randomly assigned into two groups: GTR and CPF groups. Measurements recorded at baseline and after surgery (6 months). Paired-T test was performed on these data. The following results were obtained after 6 months: In both groups significant reduction in probing pocket depth were measured in GTR and CPF groups, 1.55 Ind 1.88 mm, respectively. Also, open vertical probing depth: 0.33, 1.11 mm. Reduction in forcation weight in both groups was 0.22 mm. Bone fill was observed in 0.33% and 51% of defects. No recession was observed in GTR group, in CPF was 0.11 mm. Loss of attached gingiva was 0.34 and 0.78 mm, respectively. No significant difference was found between clinical parameters except OHPD. Comparison of means at the day (0 and 180) in each group showed the success for regeneration of forca. Considering the results, it can be concluded that CPF may substitute for GTR technique.